2022
DOI: 10.1177/21582440221094591
|View full text |Cite
|
Sign up to set email alerts
|

Decent Work and Turnover Intention Among New Generation Employees: The Mediating Role of Job Satisfaction and the Moderating Role of Job Autonomy

Abstract: New generation employees have become a major force in the workplace, and their high turnover rate is a major issue in academia and business. Drawing from the psychology of working theory and the job characteristics model, this study aims to explore the influence of decent work on new generation employees’ turnover intention and the roles of job satisfaction and job autonomy in this relationship. After collecting a sample of 391 new generation employees in China through online questionnaires, we utilized SPSS 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 60 publications
5
28
0
1
Order By: Relevance
“…Second, general well-being was also found to negatively predict turnover intentions and acted as a significant mediator linking decent work and turnover intentions. Previous studies on the mediator linking work-related variables and turnover intentions have been limited to variables like job embeddedness (Hassan et al, 2021) and job satisfaction (Wan & Duffy, 2022). However, well-being, integrating life, work and psychological elements, is in a better position to explain how decent work is related to millennial employees’ turnover intentions than just job-related variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, general well-being was also found to negatively predict turnover intentions and acted as a significant mediator linking decent work and turnover intentions. Previous studies on the mediator linking work-related variables and turnover intentions have been limited to variables like job embeddedness (Hassan et al, 2021) and job satisfaction (Wan & Duffy, 2022). However, well-being, integrating life, work and psychological elements, is in a better position to explain how decent work is related to millennial employees’ turnover intentions than just job-related variables.…”
Section: Discussionmentioning
confidence: 99%
“…To explore this question, scholars have attempted to analyze the predictors of millennials' turnover intentions and they have found that one of the most consistent factors is related to the work itself (Hassan et al, 2021). A recent empirical research by Wan and Duffy (2022) showed that if millennial employees cannot access to decent work, they are quite likely to feel unsatisfied with their job and report a high likelihood of leaving their current organization. Psychology of working theory (PWT), an emerging theory within the field of vocational psychology, is a useful framework to draw from in considering why these two variables may be linked.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous research emphasizes that decent work achieves physical and mental health and well-being through need satisfaction from the perspective of vocational psychology. 6,11,58 Only a small number of studies have investigated the relationship between decent work and workplace outcomes, specifically in terms of employee performance, 7 innovative work behavior, 12 turnover intention, 17 and proactive behaviors. 13 Previous studies have not theoretically or empirically tested the potential negative impact of decent work on workplace deviance, nor have they considered the potential role of relative deprivation in the relationship between them.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…11,16 Therefore, it is crucial to examine the negative aspects of decent work to gain a more comprehensive understanding of its impact on employees in various work settings. 17 Burnout and work fatigue represent the loss of a healthy working state, while workplace deviance is a violation that further harms the organization 3 rather than an internal mental friction. Currently, there is a lack of literature examining the potential impact of decent work on workplace deviance.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the background mentioned above, our research was primarily motivated by the lack of empirical studies testing the hypothesized relationships of the PWT among its intended target sample (i.e., working class) and the shortage of decent work studies stemming from non-western countries such as South Africa. Furthermore, the study builds on the recent work of Wan and Duffy (2022a), as their findings have opened the door for future studies to explore outcomes of decent work and the role of job satisfaction within the PWT more closely. The aim of our study was two-folded: 1) to provide empirical evidence for the hypothesized PWT relationships among blue-collar workers within a non-Western context such as South Africa, and 2) to expand our knowledge on the outcome portion of the PWT by incorporating subjective career success and exploring the mediating role of job satisfaction in this regard.…”
Section: The Present Studymentioning
confidence: 99%